Dr. B.R. Ambedkar's Interpretation of the Doctrines of Karma and Rebirth - Kumar, Bimalendra (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
Background: This paper analyzes Dr. B.R. Ambedkar's interpretation on the doctrine of karma and rebirth in Buddhism. Dr. Ambedkar, obviously, accepts the traditional Buddhist concept regarding karma and rebirth but he forwards his different opinion that the body upon the dissolution gets its Mahabhuts (Prithvi, Agni, jal, Vayu) stored in the respective Mahabhuts in the Universe. Objective: The paper is meant for clarifying Ambedkar's idea on karma and rebirth. It is to prove that the agrigates of a being get mixed into the mega agrigates in the universe during the time of death; and at the time of rebirth, the agrigates get reassembled with karmic consciousness, and there the being gets rebirth based on the past karma. Methodology: Library based Interpretive or Analytical approach is adopted to carry out the research. Result: Through the study it has been found that at the time of rebirth, the Mahabhuts including the elements like heat and consciousness come back to the mother's womb to get assembled and there the new being gets delivered on the planet together with the fruits of its old karma. Ambedkar relates karma and rebirth to modern science explaining 'Rebirth' as a cycle of physical elements, instead of the wandering soul. It is shown how Ambedkar reinterprets the traditional Buddhist ideas to fit with the conceptions of modern science and philosophy in the article. Conclusion: The Paper forwards the idea of Ambedkar that there is no rebirth of the soul but regeneration of the matter or element. There is the possibility of the fruit or retribution of the moral or immoral actions done by a person as the new being gets its old elements assembled during the time of rebirth.